THE INFLUENCE OF THE INDEPENDENT LEARNING CURRICULUM ON STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Nurohmat Nurohmat; Dian; Sisca T. Gurning (JEELL (Journal of English Education, Linguistics and Literature), 2025)
The aim of this study is to examine the impact of Indonesia's Independent Learning Curriculum (Merdeka Curriculum) on the English learning achievement of vocational school students in West Jakarta. A quantitative research approach, including standardized English proficiency tests and surveys, was employed to assess the differences in achievement. The results show that students under the Independent Learning Curriculum achieved significantly higher scores in English proficiency, particularly in speaking and writing, compared to those following the previous 2013 curriculum. The improved outcomes are attributed to the curriculum's flexibility, focus on 21st-century skills, and integration of technology. However, successful implementation depends on factors such as teacher quality, school facilities, and stakeholder involvement. This study contributes to the ongoing discourse on curriculum reform and its effects on student learning outcomes in vocational education in Indonesia.